The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1183/09031936.00130913
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep apnoea is associated with major cardiac events in peripheral arterial disease

Abstract: Obstructive sleep apnoea (OSA) is associated with atherosclerosis and cardiovascular events. Peripheral arterial disease (PAD) represents severe atherosclerosis with a high mortality after vascular surgery. The role of OSA in the prognosis of these patients is not yet established.84 patients (aged 67¡9 years) scheduled for sub-inguinal surgical revascularisation were enrolled for preoperative polysomnography. The threshold for significant OSA was an apnoea/hypopnoea index o20 events?h -1 . Major adverse cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In patients with OSAS with significant characteristics of upper airway collapse (19) and effects on the circulatory system, the primary mechanism involves the excitement of sympathetic nerves (3), increase of endothelin levels (20), vascular endothelial function, abnormalities in vascular active substances (21), vascular tension (22) and excessive renin secretion causing sustained hypertension (23). In previous studies, plasma levels of CRP and other inflammatory cytokines in patients with OSAS caused by inflammation have been reported to promote cardiovascular and cerebrovascular diseases (24), including AS.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with OSAS with significant characteristics of upper airway collapse (19) and effects on the circulatory system, the primary mechanism involves the excitement of sympathetic nerves (3), increase of endothelin levels (20), vascular endothelial function, abnormalities in vascular active substances (21), vascular tension (22) and excessive renin secretion causing sustained hypertension (23). In previous studies, plasma levels of CRP and other inflammatory cytokines in patients with OSAS caused by inflammation have been reported to promote cardiovascular and cerebrovascular diseases (24), including AS.…”
Section: Discussionmentioning
confidence: 99%
“…In a 1-year follow-up study in 84 patients undergoing surgical revascularization for peripheral artery disease, an AHI $ 20 was predictive of major adverse cardiovascular and cerebrovascular events (hazard ratio, 5.1). 35 Lastly, a study in 471 patients who had undergone various noncardiac or upper airway surgeries under general anesthetic, Kaw et al 36 reported that a diagnosis of OSA (as defined by an AHI $ 5 events per hour) was associated with increased risk of postoperative hypoxemia, admission to the ICU, and longer hospital length of stay. No relationship between the AHI and postoperative complications was reported.…”
Section: Apnea-hypopnea Indexmentioning
confidence: 99%
“…A further 525 records were removed after screening by titles and abstracts. We carefully read the full texts of the remaining 16 papers and then excluded 8 additional articles [11][12][13][14][15][16][17][18] for the following reasons: (1) a review, (2) no extractable data, (3) overlapping data, (4) Burger disease, and (5) PAD not clearly identified as a cardiovascular event. Ultimately, the review included 8 articles.…”
Section: Search Resultsmentioning
confidence: 99%